2005
DOI: 10.1111/j.1365-3083.2005.01564.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐Cell Receptor Vβ Repertoire after Myeloablative and Reduced Intensity Conditioning Allogeneic Haematopoietic Stem Cell Transplantation

Abstract: T cells play an important role in the adaptive immune system. After haematopoietic stem cell transplantation (HSCT), T-cell function is impaired. This is reflected by the emergence of opportunistic infections, infections that are often difficult to treat because of the patient's insufficient immune function. T-cell receptor reconstitution was studied using CDR3 spectratyping to analyze the diversity of the T-cell repertoire at 3, 6 and 12 months after myeloablative and reduced intensity conditioning (RIC) HSCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…However, Bahceci et al [5] reported that T-cell repertoire after nonmyeloablative peripheral blood stem cell transplantation was unaffected by GVHD. Hentschke et al [12] also found no difference in diversity score between patients with acute GVHD grades 0, I, and II. They explained that although GVHD might lead to thymic injury, thymus did not seem to have a measurable contribution to T-cell recovery in adults early after HSCT, and the early recover of T-cell compartment was via peripheral expansion [5,30].…”
Section: Discussionmentioning
confidence: 93%
“…However, Bahceci et al [5] reported that T-cell repertoire after nonmyeloablative peripheral blood stem cell transplantation was unaffected by GVHD. Hentschke et al [12] also found no difference in diversity score between patients with acute GVHD grades 0, I, and II. They explained that although GVHD might lead to thymic injury, thymus did not seem to have a measurable contribution to T-cell recovery in adults early after HSCT, and the early recover of T-cell compartment was via peripheral expansion [5,30].…”
Section: Discussionmentioning
confidence: 93%
“…The markedly skewed profile detected in the Tconv subpopulation resembled the features described early after allografting in the CD4 + subset, in which the repertoire reconstitutes within 3 years. [3][4][5] In fact, after 3 years, the TCR Vβ profiles of the two cell subsets tended to become identical, paralleling the Tconv subset recovery. The much higher degree of TCR similarity between the two cell subsets observed in patients more than 3 years after SCT as compared to those with a more recent transplant could reflect the kinetics of reconstitution of the whole Tcell compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the requirement for thymic maturation 29 could further contribute to altering the repertoire of Treg, as has been found for conventional T cells. [3][4][5] Although it is well known that the repertoire of antigen specificities of Treg in mice is as broad as that of naive T cells, 30 only two studies have been conducted in humans. 31,32 In normal subjects the TCR repertoire of Treg appears to be similar to that of the CD25 -counterpart, thus suggesting the recognition of a similar spectrum of antigens.…”
Section: 19mentioning
confidence: 99%
“…1 Reduced intensity conditioning (RIC) regimens may be associated with more rapid immunologic reconstitution than myeloablative conditioning via mechanisms such as the preservation of T-celldependent mitogenic responses 2 , thymic function 3 and increased early T-cell repertoire complexity. 4 Other studies have not demonstrated significantly improved immune reconstitution with RIC, 5,6 making this area a subject of continued debate (reviewed by Jimenez et al 7 ). While many previous studies of immune reconstitution post HSCT have focused on lymphocyte subset recovery, [8][9][10][11][12][13][14][15][16] we have previously shown that combined monocyte and lymphocyte recovery also has an impact on survival post myeloablative HSCT in acute leukemia due to a reduction in nonrelapse mortality.…”
Section: Introductionmentioning
confidence: 99%